“A hazy world seen through smoke”: Threshold Effects in Mohsin Hamid’s Moth Smoke - Maëlle Jeanniard du Dot (Angles)
This article proposes to analyse Mohsin Hamid’s first novel Moth Smoke (2000) through the motif of the threshold. Moth Smoke tells the story of a crime and its judgment through a multiplicity of voices. The novel takes place in spring 1998, as Pakistan’s nuclear tests are about to be launched. In this novel, the notion of threshold unfolds thematically as an expression of Pakistani society’s inherent divisions. It can be both a hindrance and a starting point which echoes the representations of time and the rising tensions of the nuclear events. The anthropological notion of liminality (from limen, the threshold) accounts for the importance of initiation (Van Gennep 1909; Turner 1966) in representations of contemporary Pakistan. The novel resorts to a number of narrative thresholds, whether they stand between the novel and its reader (Genette 1997), or between different parts of the story, displaying Mohsin Hamid’s characteristic use of gaze-shifting and displacement.